A new technique for remote sensing of O2 density from 140 to 180 km. Issue 2 (23rd January 2015) - Hecht, James H.; Christensen, Andrew B.; Yee, Jeng‐Hwa; Crowley, Geoff; Bishop, Rebeeca L.; Budzien, Scott A.; Stephan, Andrew W.; Evans, J. Scott
Abstract: Observations of molecular oxygen are difficult to make in the Earth's atmosphere between 140 and 200 km altitude. Perhaps the most accurate measurements to date have been obtained from satellite instruments that measure solar occultations of the limb. These do provide height‐resolved O2 density measurements, but the nature of this technique is such that the temporal/spatial distribution of the measurements is uneven. Here a new space‐based technique is described that utilizes two bright dayglow emissions, the (0, 0) transition of the O2 atmospheric band and the O I (630 nm), to derive the height‐resolved O2 density from 140 to 180 km. Data from the Remote Atmospheric and Ionospheric Detection System, which was placed on the International Space Station in late 2009, are used to illustrate this technique. The O2 density results for periods in May 2010 that were geomagnetically quiet and disturbed are compared to model predictions. Key Points: New simple technique described to measure O2 density from 140 to 200 km Technique is demonstrated using RAIDS Space Station data Results show dynamical changes not fully captured by models